PEMANFAATAN KONTEN YOUTUBE SEBAGAI MEDIA BANTU PEMAHAMAN KITAB GUNDUL PADA MAHASISWA PENDIDIKAN BAHASA ARAB - Nadia Tasya Firdausi (Al Ibrah: Journal of Arabic Language Education, 2026)
This study examines the utilization of YouTube content as a learning aid for understanding kitab gundul (unvowelized Arabic texts) among Arabic Language Education students at Hasyim Asy'ari University Tebuireng Jombang. The increasing use of social media among university students provides an opportunity to leverage digital content as a supplementary learning resource, particularly for courses that use Arabic texts without diacritical marks and translations. This study employed a qualitative descriptive approach with a case study design. Data were collected through semi-structured interviews and observation involving three first-semester students of the Arabic Language Education program who actively used social media as a learning resource. Data were analyzed using an interactive analysis model comprising data reduction, data presentation, and conclusion drawing. Trustworthiness was ensured through source triangulation. The results indicate that YouTube, particularly the Wasiltunaa channel, was the primary platform utilized by students to support their understanding of kitab gundul materials in the Qawa'id al-Imla' al-'Arabiyyah course. Three key themes emerged: (1) YouTube as a structured comprehension aid for unvowelized Arabic texts, (2) improvement of learning motivation and independent learning, and (3) challenges in selective and critical use of digital content. This study concludes that YouTube content has significant potential as a supplementary medium in Arabic language learning when used purposefully and critically.Penelitian ini mengkaji pemanfaatan konten YouTube sebagai media bantu pemahaman kitab gundul pada mahasiswa Pendidikan Bahasa Arab Universitas Hasyim Asy'ari Tebuireng Jombang. Meningkatnya penggunaan media sosial di kalangan mahasiswa membuka peluang pemanfaatan konten digital sebagai sumber belajar tambahan, khususnya pada mata kuliah yang menggunakan teks bahasa Arab tanpa harakat dan terjemahan. Penelitian ini menggunakan pendekatan deskriptif kualitatif dengan desain studi kasus. Data dikumpulkan melalui wawancara semi-terstruktur dan observasi terhadap tiga mahasiswa semester satu Program Studi Pendidikan Bahasa Arab yang aktif memanfaatkan media sosial sebagai sumber belajar. Data dianalisis menggunakan model analisis interaktif yang meliputi reduksi data, penyajian data, dan penarikan kesimpulan. Keabsahan data dijamin melalui triangulasi sumber. Hasil penelitian menunjukkan bahwa YouTube, khususnya kanal Wasiltunaa, menjadi platform utama yang dimanfaatkan mahasiswa untuk mendukung pemahaman materi kitab gundul pada mata kuliah Qawa'id al-Imla' al-'Arabiyyah. Tiga tema utama yang ditemukan: (1) YouTube sebagai media bantu pemahaman teks Arab tanpa harakat secara terstruktur, (2) peningkatan motivasi belajar dan kemandirian belajar mahasiswa, serta (3) tantangan dalam penggunaan konten digital secara selektif dan kritis. Penelitian ini menyimpulkan bahwa konten YouTube berpotensi besar sebagai media pendukung dalam pembelajaran bahasa Arab apabila digunakan secara terarah dan kritis.